A proteção multinível dos direitos sociais: verticalidade gótica ou horizontalidade renascentista? – Do não impacto da Carta Social Europeia (Revista) na jurisprudência constitucional portuguesa - Botelho, Catarina Santos (2017)
A comparative constitutional law analysis reveals considerable differences in the treatment, either quantitative or qualitative, that the member states of the Council of Europe grant to social rights. In Portugal, it seems indisputable that the Revised European Social Charter (RESC) did not have a significant impact on constitutional jurisprudence. In this context it is legitimate to question to what extent does the RESC somehow live in the shadow of the European Convention on Human Rights, as the 'ugly duckling' of the Council of Europe. In our perspective, the absence of a genuine international complaint mechanism in the field of social rights contributes to the normative weakening of the RESC and to the perception that its effectiveness is reduced - albeit unconsciously - to being merely proclamatory